Pengaruh Kontribusi Konformitas Peer Group dan Pemanfaatan Fitur Live Streaming sebagai Media Marketing dalam Melakukan Consumer Purchasing Decisions pada E-Commerce Shopee dalam Perspektif Bisnis Islam - Dita Eka Oktaviani; Tulus Suryanto; Nurhayati Nurhayati (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This research is motivated by technological advances in the digital era that continue to grow. The rise of e-commerce in Indonesia has also caused business actors and MSMEs to migrate offline sales and marketing systems to online systems. This research uses quantitative methods. The population in the study was shopee e-commerce users. The sample used was purposive sampling, with 100 respondents determined using the lemeshow formula. The results showed that peer group conformity (X1) had a positive and significant effect on consumer purchasing decisions (Y) in shopee e-commerce. The live streaming feature variable (X2) has a positive and significant effect on consumer purchasing decisions (Y) in shopee e-commerce. The results showed that peer group conformity (X1) and live streaming features (X2) had a positive and significant effect on consumer purchasing decisions (Y) in shopee e-commerce. In the view of Islam, when making purchasing decisions, you should not accept the news conveyed by someone directly but check the truth first. Muslim traders in carrying out online buying and selling must comply with the provisions of the DSN-MUI Fatwa when making sales there is no element of tadlis.